Elevated sperm DNA fragmentation is correlated with an increased chromosomal aneuploidy rate of miscarried conceptus in women of advanced age undergoing fresh embryo transfer cycle - Fu, Wanting; Cui, Qiuying; Bu, Zhiqin; Shi, Hao; Yang, Qingling; Hu, Linli (Frontiers in Endocrinology, 2024)
Background: Male sperm DNA fragmentation (SDF) may be associated with assisted reproductive technology (ART) outcomes, but the impact of SDF on the occurrence of aneuploid-related miscarriage remains controversial.Genome-wide single-nucleotide polymorphism-based chromosomal microarray analysis was performed on 495 miscarried chorionic villus samples undergone IVF/ICSI treatment from the Reproductive Medicine Center of the First Affiliated Hospital of Zhengzhou University. SDF was assessed using sperm chromatin 2 structure assay. Patients were divided into four groups according to embryo transfer cycle type and maternal age, and the correlation between SDF and chromosome aberration was analyzed. A receiver operating characteristic (ROC) curve was utilized to find the optimal threshold.Results: Total chromosomal aneuploidy rate was 54.95%, and trisomy was the most common abnormality (71.32%). The chromosomally abnormal group had higher SDF than the normal group (11.42% [6.82%, 16.54%] vs. 12.95% [9.61%, 20.58%], P = 0.03215.91% ± 12.36% vs. 13.46% ± 9.74%, P = 0.018). After grouping, elevated SDF was significantly correlated with an increasing chromosome aneuploidy rate only in women of advanced age who underwent fresh embryo transfer (adjusted odds ratio:1.14 [1.00-1.29], adjusted-P = 0.045). The receiver operating characteristic curve showed that SDF can predict the occurrence of chromosomal abnormality of miscarried conceptus in this group ((area under the curve = 0.76 [0.60-0.91], P = 0.005), and 8.5% was the optimum threshold. When SDF was ≥ 8.5%, the risk of such patients increased by 5.76 times (adjusted odds ratio: 6.76 [1.20-37.99], adjusted-P = 0.030).For women of advanced maternal age undergoing fresh embryo transfer, older oocytes fertilized using sperm with high SDF in IVF/ICSI treatment might increase the risk of chromosomal abnormality in miscarried conceptus.